Facile Synthesis of Chiral Diphosphine-Containing Multiple Dendrimeric Catalysts for Enantioselective Hydrogenation - 赵立文 刘继 冯宇 何艳梅 范青华 (Chinese journal of chemistry, 2012)
A new kind of chiral diphosphine PyrPhos-functionalized codendrimers have been synthesized via a liq- uid-phase strategy in high yields. The resulting dendrimeric PyrPhos ligands were purified by a simple solvent pre- cipitation without the need for chromatographic separation, and well characterized by 1H, 13C and 31p NMR, MALDI-TOF mass spectroscopy as well as elemental analysis. Their rhodium complexes were applied to the asymmetric hydrogenation of a-acetamido cinnamic acids. Excellent enantioselectivities were achieved, which are comparable to those with the corresponding small molecular catalysts. In addition, these codendrimeric catalysts showed better catalytic performance than the dendrimeric catalysts with Rh（PyrPhos） sites located in the focal point ofpoly（aryl ether） dendrons or in the periphery ofpoly（propyleneimine） dendrimers.